Production of casting auxiliaries from plastpolymer materials - S. L. Rovin; L. A. Nelub (Литьë и металлургия)
In the article there are examined the questions of the plasto-polymer model auxiliaries production, which allows to reduce the time of the casting production preparation in 5-10 times.